2019
DOI: 10.1038/s41467-019-11780-y
|View full text |Cite
|
Sign up to set email alerts
|

An electrostatic switching mechanism to control the lipid transfer activity of Osh6p

Abstract: A central assumption is that lipid transfer proteins (LTPs) bind transiently to organelle membranes to distribute lipids in the eukaryotic cell. Osh6p and Osh7p are yeast LTPs that transfer phosphatidylserine (PS) from the endoplasmic reticulum (ER) to the plasma membrane (PM) via PS/phosphatidylinositol-4-phosphate (PI4P) exchange cycles. It is unknown how, at each cycle, they escape from the electrostatic attraction of the PM, highly anionic, to return to the ER. Using cellular and in vitro approaches, we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 75 publications
(123 reference statements)
7
39
0
Order By: Relevance
“…In this regard, we reported an apparent affinity of SWG for the ORD in the presence of detergent micelles of Kd~35 nM, which is rather low compared to the measured Ki. Akin to what has been observed recently on Osh6 (29), the ORD lid is probably unlocked by the interfacial micellar environment, hence leading to faster exchange kinetics and lower affinities. Further studies of the kinetics of SWG binding to or dissociation from the ORD with liposomes of defined composition should give information on the interfacial interactions involved in lipid exchange.…”
Section: Discussionsupporting
confidence: 59%
“…In this regard, we reported an apparent affinity of SWG for the ORD in the presence of detergent micelles of Kd~35 nM, which is rather low compared to the measured Ki. Akin to what has been observed recently on Osh6 (29), the ORD lid is probably unlocked by the interfacial micellar environment, hence leading to faster exchange kinetics and lower affinities. Further studies of the kinetics of SWG binding to or dissociation from the ORD with liposomes of defined composition should give information on the interfacial interactions involved in lipid exchange.…”
Section: Discussionsupporting
confidence: 59%
“…In contrast, Osh6 consists only of an ORD and how it targets the ER and the PM is not known. We have previously demonstrated that to some extent, the cellular localization of Osh6 is regulated by its intrinsic avidity for lipid membranes (Lipp et al, 2019). However, this does not explain how Osh6 specifically targets its donor and acceptor compartments and how it maintains accuracy in PS transport.…”
Section: Introductionmentioning
confidence: 95%
“…We therefore wanted to map the Ist2-interaction site on Osh6. Previous work revealed key residues (H157/H158 and L69) that coordinate the lipid ligand inside the binding pocket, and the importance of the N-ter region (1-69), which forms a lid over the binding pocket and regulates Osh6 interaction with lipid membranes (Maeda et al, 2013;Lipp et al, 2019). Mutation or deletion of these residues did not affect Osh6-Ist2 interaction ( Fig.…”
Section: Mapping the Ist2 Interaction Site On Osh6mentioning
confidence: 86%